1992
DOI: 10.1002/jor.1100100117
|View full text |Cite
|
Sign up to set email alerts
|

Colony‐forming efficiency response of bone marrow stromal cells to acute blood loss

Abstract: Colony-forming efficiency (CFE) was used to monitor the proliferative response of alkaline phosphatase-positive rabbit bone marrow stromal cells to acute blood loss. The CFE of animals subjected to a 1% blood loss was 0.97 compared with 0.06 (p less than 0.01) in nonbled animals. Sera obtained from animals 10 days after an initial blood loss stimulated the CFE of marrow cultures from nonbled donors to the same degree as osteogenin. Erythropoietin and control sera (from nonbled animals) had no effect. Hence, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…This suggested a link between the haematopoietic activity of the iliac crest and osteogenesis localized around the focus of the osteotomy. This phenomenon has been confirmed by experiments in rats and mice by Bab [13] and in rabbits by Lippiello [14]. Animal studies done by Kadiyala et al (1997) on rat femora demonstrated that purified, culture-expanded syngeneic progenitor cells were capable of healing a clinically significant bone defect within 8 weeks [15].…”
Section: Introductionmentioning
confidence: 79%
“…This suggested a link between the haematopoietic activity of the iliac crest and osteogenesis localized around the focus of the osteotomy. This phenomenon has been confirmed by experiments in rats and mice by Bab [13] and in rabbits by Lippiello [14]. Animal studies done by Kadiyala et al (1997) on rat femora demonstrated that purified, culture-expanded syngeneic progenitor cells were capable of healing a clinically significant bone defect within 8 weeks [15].…”
Section: Introductionmentioning
confidence: 79%
“…Some authors have been conducting experiments in an attempt to isolate substances produced on bodies, which would supposedly be correlated to bone formation. [8][9][10][11][12][13][14]22 In this experiment, three groups of animals were used: group A, submitted to ostectomy and to bone marrow remote stimulation by ablation, in order to assess the systemic osteogenic response after an intensive bone marrow regeneration process; group B, submitted to ostectomy and to bone marrow remote stimulation by placing a Kirschner wire inside the bone marrow in order to assess the systemic osteogenic response after an intensive bone marrow regeneration process , and; group C -control group -which was used for comparison. On the three groups, we performed blood depletion and used a garrote on the operated limb with an elastic band in order to reduce bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The systemic osteogenic response was observed after stimuli distant from the fracture focus, such as in bone marrow injuries [4][5][6][7][8] and/or blood leakage 9,10 . Tavares et al 4 described a faster union in rabbits submitted to radius ostectomy associated to remote bone marrow stimulus, by placing a Kirschner wire at the femoral intramedullary space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to nonbled rabbits, the bled rabbits showed higher CFU efficiency. Lippiello also suggested that the colony forming efficiency response of bone marrow cells to blood loss is associated with increases of a bone growth promoting circulating factor that mimics the activity of osteogenin (bone morphogenetic protein 3) (44).…”
Section: Acute Blood Lossmentioning
confidence: 99%